Democratizing the Hegemonic State : Political Transformation in the Age of Identity - Peleg Ilan (Cambridge University Press, 2007)
This book explores alternative ways of solving political conflicts between ethnic groups in deeply divided societies. Through a detailed analysis of 14 different countries in Africa, Asia, Europe, North America, and the Middle East, Peleg creates a framework that will allow humanity to move toward a solution to some of the bloodiest conflicts in history. Long-lasting solutions cannot be found by merely granting individuals equal rights, but by recognizing the rights of distinct groups. This book examines the most important political and ethical issue of the contemporary world: the future of deeply divided societies dominated by ethnic politics.